A modeling methodology to facilitate safety‐oriented architecture design of industrial avionics software‡. (2nd July 2014) - Wu, Ji; Yue, Tao; Ali, Shaukat; Zhang, Huihui; Tse, T. H.; Gotlieb, Arnaud; Chen, Zhenyu
Summary Ensuring that avionics software meets safety requirements at each development stage is very important to warrant the safe operation of an avionics system. Many safety requirements are imposed by various standards and industrial regulations that must be met by avionics software. One of such standards is DO‐178B/C, which provides guidelines (e.g., development process and objectives to satisfy in development activities) for meeting safety requirements. This paper presents a modeling methodology including a UML profile for specifying safety requirements on a component‐based architecture model and a set of design guidelines on avionics software. These safety requirements were identified from both standards (mainly DO‐178B/C) and current engineering practices in the domain of avionics systems. The methodology automatically enforces these safety requirements. We have applied the methodology on an industrial autopilot system, and several previously uncaught faults were revealed. Copyright © 2014 John Wiley & Sons, Ltd.